Fisheries issue in the Central Arctic Ocean and its future governance. Issue 2 (3rd July 2017) - Min, Pan
Abstract: The Central Arctic Ocean (CAO) is a global commons and fishes in the CAO are common property resources. If humanity does not manage this region well, it will lead to a "tragedy of the commons." However, the two existing means of commons' governance, privatisation or government control, are not appropriate for the CAO. According to my research, CAO fisheries management will most likely come out of a process of self-organisation. The openness of the CAO, the imbalance of powers, interests and responsibilities among the states that are involved; are likely to lead to a process of self-organised governance of the CAO fisheries. There are four stages in the process: competition, synergy, establishment of governing principles and mechanisms, and expanding and evolving influence. The likely outcome of CAO fisheries governance will be the result of gamesmanship among the parties as no one actor is in a dominant position.